698 FO05 – Characteristics of potential head injury situations at the FIFA world cup Qatar 2022 - Peek, Kerry; Aiello, Francesco; Avery, Lewis; Harvey, Tom; Rutherford, Harvey; Massey, Andrew; Georgieva, Julia; Andersen, Thor Einar; Dahlén, Sara; Serner, Andreas (British journal of sports medicine, 2024)
BackgroundWith increasing global concern regarding the short- and long-term consequences of head injuries in football there’s a need to explore the characteristics of potential head injury situations as an essential part of the injury prevention continuum.ObjectiveTo review characteristics of potential head injury situations during a professional men’s international football tournament.DesignFor this descriptive study analysts coded each potential head injury situation from 64 matches of the FIFA World Cup Qatar 2022™ using the FIFA Football Language-Medical coding. Potential head injury situations were coded when a player stayed down for more than five seconds and/or requested medical attention, and where the body location included the player’s head. Characteristics were further coded for variables pertaining to the match, player, player action (including aerial duels), outcome of the event and time taken to reach an outcome.SettingVideo analysisParticipantsFrom 680 players who played in at least one match at the FIFA World Cup, 117 (17%) were involved in a potential head injury situation. This included 96 players who were involved in 1 potential head injury situation and 21 players involved in 2–4 potential head injury situations.ResultsIn total, 149 potential head injury situations occurred in 56 matches (mean 2.33/match, range 0–6). Players were more likely to be involved in a potential head injury situation through direct player-player contact when the ball was loose (not in any team’s possession), and two players were jumping in an aerial duel. An injury stoppage with on-pitch medical assessment occurred for 35 potential head injury situations (23%), with pitch-side assessment also occurring in 15 situations (10%). Four concussion substitutions were utilised throughout the tournament.ConclusionGiven the risk associated with player-to-player contact during aerial duels, teaching players appropriate awareness and body positioning would appear justified as a primary injury prevention strategy.